Introduction for The Special Section On "Inclusive, Circular, And Technological Transformations in Financial Accounting: Challenges and Opportunities for Organizations and Stakeholders" - Feten Arfaoui-Masmoudi; Sourour Hazami-Ammar (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research question- How accounting research can address the relevant issues of inclusivity, circularity, and technological transformation? Motivation- This editorial introduces a Special Section addressing inclusivity, circularity, and technological transformation. The Special Section aims to inform policy, improve organizational practices, and inspire future research, contributing to a more sustainable and inclusive future for all stakeholders. Data- The editorial relies on key papers to motivate the topics addressed and then introduces the content of the papers selected for publication. Findings- The papers included in the Special Section not only address the theoretical foundations of these topics but also offer practical insights and recommendations. By doing so, they aim to spark meaningful discussions and inspire action among policymakers, practitioners, and researchers committed to promoting a sustainable and inclusive global economy.
Keywords: M41; 650; inclusivity; circularity; technological transformation; accounting